THE INFLUENCE OF SOCIAL MEDIA PROMOTION AND BRAND AWARENESS ON PURCHASE INTENTION: A STUDY ON MAYBELLINE CONSUMERS - Putri, Azzahra Aulia Suhendra; Santhuso, Agus (Fakultas Ekonomi dan Bisnis Universitas Islam As-Syafi'iyah, 2025)
This study aims to analyze the influence of social media promotion and brand awareness on consumers’ purchase intention of Maybelline cosmetic products in the Pondok Bambu area, East Jakarta. The phenomenon of declining demang for Maybelline products in 2023 serves as an important background for this research, especially amid the widespread use of social media as a promotional tool and the growing competition among cosmetic brands. This research adopts a quantitative approach using a survey methode involving 140 respondents who are consumers of Maybelline products. The data analysis technique used is multiple linear regressione to examine the effect of each independent variable on the dependent variable. The results show that social media promotion has a significant negative effect on purchase intention, while brand awareness has a significant positive effect on consumers’ purchase intention. These findings indicate that through promotion is carried out extensively, if it does not align with audience preferences or is too repetitive, it encourages consumers’ tendency to buy the product. These results are expected to serve as a reference for developing more relevant marketing strategies focused on the quality of promotional content and brand strengthening.